Ordering‐Dependent Hydrogen Evolution and Oxygen Reduction Electrocatalysis of High‐Entropy Intermetallic Pt 4 FeCoCuNi - Wang, Yong; Gong, Na; Liu, Hongfei; Ma, Wei; Hippalgaonkar, Kedar; Liu, Zheng; Huang, Yizhong (Advanced materials (Weinheim), 2023)
Disordered solid‐solution high‐entropy alloys have attracted wide research attention as robust electrocatalysts. In comparison, ordered high‐entropy intermetallics have been hardly explored and the effects of the degree of chemical ordering on catalytic activity remain unknown. In this study, a series of multicomponent intermetallic Pt 4 FeCoCuNi nanoparticles with tunable ordering degrees is fabricated. The transformation mechanism of the multicomponent nanoparticles from disordered structure into ordered structure is revealed at the single‐particle level, and it agrees with macroscopic analysis by selected‐area electron diffraction and X‐ray diffraction. The electrocatalytic performance of Pt 4 FeCoCuNi nanoparticles correlates well with their crystal structure and electronic structure. It is found that increasing the degree of ordering promotes electrocatalytic performance. The highly ordered Pt 4 FeCoCuNi achieves the highest mass activities toward both acidic oxygen reduction reaction (ORR) and alkaline hydrogen evolution reaction (HER) which are 18.9‐fold and 5.6‐fold higher than those of commercial Pt/C, respectively. The experiment also shows that this catalyst demonstrates better long‐term stability than both partially ordered and disordered Pt 4 FeCoCuNi as well as Pt/C when subject to both HER and ORR. This ordering‐dependent structure–property relationship provides insight into the rational design of catalysts and stimulates the exploration of many other multicomponent intermetallic alloys.